Hermeneutics, religion, and ethics - Gadamer, Hans-Georg, 1900-2002 (Yale studies in hermeneutics., 1999)
"In the years shortly before and after the publication of his classic Truth and Method (1960), the eminent German philosopher Hans-Georg Gadamer returned often to questions surrounding religion and ethics. In this selection of writings from Gesammelte Werke that are here translated into English for the first time, Gadamer probes deeply into the hermeneutic significance of these subjects."--Jacket